Identification of miRNA-34a and miRNA-155 as prognostic markers for mantle cell lymphoma - Jianxia He; Yanfeng Xi; Ning Gao; Enwei Xu; Jin Chang; Jie Liu (Journal of International Medical Research, 2021)
Objective MicroRNAs (miRNAs) with functional relevance have not been previously identified in mantle cell lymphoma (MCL). Here, we aimed to evaluate the relationships between miR-34a and miR-155-5p and MCL clinicopathology and prognosis. Methods Seventy-five paraffin-embedded tissue samples from patients with MCL who completed at least four cycles of chemotherapy from January 2006 to October 2016, and 27 samples from control patients with reactive lymphoid hyperplasia (RLH), were collected. MiRNA expression levels were measured by qRT-PCR. Results The miR-155-5p levels were significantly higher in patients with MCL than in the controls. The Eastern Cooperative Oncology Group (ECOG) ≥ 2 and Sex-Determining Region Y-Box transcription factor 11 (SOX11) < median value (M) groups presented lower miR-34a expression than the ECOG < 2 and SOX11 ≥ M groups, respectively. MiR-155-5p expression differed between low, intermediate, and high MCL International Prognostic Index risk groups. The AUCs of miR-34a and miR-155-5p were 0.5819 and 0.7784, respectively. The median survival times of the miR-34a ≤ 0.2150 and miR-155-5p > 2.11 groups were shorter than those of the miR-34a > 0.2150 and miR-155-5p ≤ 2.11 groups, respectively. Conclusions Low miR-34a and elevated miR-155-5p levels may be correlated with poor prognosis in MCL.